Global DNA hypomethylation is an early event in Helicobacter pylori-related gastric carcinogenesis. Issue 8 (26th May 2011) - Compare, Debora; Rocco, Alba; Liguori, Eleonora; D'Armiento, Francesco Paolo; Persico, Giovanni; Masone, Stefania; Coppola-Bottazzi, Enrico; Suriani, Renzo; Romano, Marco; Nardone, Gerardo
Abstract : Aim: Cancer, particularly gastric cancer (GC), is prevalently an epigenetic phenomenon that is dependent on an altered DNA methylation pattern. In gastric carcinogenesis, many genes show aberrant methylation; however, none of them may be used as a biomarker of cancer risk and progression. The authors aimed to evaluate the global DNA methylation of gastric mucosa in Helicobacter pylori ( Hp )-related chronic gastritis, in GC and in 10 patients with preneoplastic lesions (ie, atrophy and intestinal metaplasia) followed up for 10 years. Methods: The authors analysed 93 dyspeptic patients who underwent upper endoscopy, 41 surgical GC samples and 10 patients with preneoplastic gastric lesions followed up for 10 years after successful Hp eradication therapy. Global DNA methylation status and surrogate markers of cell proliferation and apoptosis were evaluated by immunohistochemistry using the anti-5-methylcytosine (5-MC), anti-Ki-67 and anti-p53 (anti-apoptotic marker)-specific antibodies, respectively. Results: Global DNA methylation of gastric mucosa gradually decreased from normal mucosa to Hp -positive gastritis, Hp -positive chronic atrophic gastritis, independent of Cag-A status and GC; however, the variation was significant (p<0.05) only between Hp -negative subjects and Hp -positive chronic gastritis. Interestingly, the 5-MC immunostaining was absent in areas of intestinal metaplasia. In the 10 patients with preneoplastic lesions, global DNA methylation decreased over time despite the eradication of Hp infection, but reached significance only at 10 years versus baseline. The 5-MC immunostaining negatively correlated with Ki-67 and p53 expression in all groups. Conclusion: Global DNA hypomethylation is an early molecular event in Hp -related gastric carcinogenesis. Further studies with more cases and a longer follow-up are needed to establish the potential GC predictive role of DNA hypomethylation.